Ha muerto el viejo y tradicional profesor (Journal of Parents and Teachers, 2014)
The author criticises the change of paradigm regarding the figure of the teacher. To do so, he takes a look at the different conceptions of the teacher that have existed over the last few years. In this way, he highlights the predominance of technology as a tool that has replaced the teacher, transmitting the necessary knowledge and skills. However, the author highlights attitudes as those that must necessarily be taught conscientiously and from a human point of view. Finally, the author invites us to reflect on the changes taking place within education.
Keywords: Teacher; Technology; Attitudes; Education; Educational changes